Video Game Navigation: A Classification System for Navigational Acts - Debus, Michael S. (Replay. The Polish Journal of Game Studies, 2017)
Navigation in video games has been a vastly neglected topic in game studies. In this paper a classification system for navigational acts has been developed through theoretical work as well as the analysis of multiple games. The result is an exclusive five-step classification system. Moreover, the development showed that navigational acts are highly dependent on the environment in which they occur. The system is a first step towards a deeper understanding of how the player navigates the gameworld, instead of what she navigates.